Cortisol reactivity and emotional memory after psychosocial stress in oral contraceptive users. Issue 1 (7th November 2016) - Mordecai, Kristen L.; Rubin, Leah H.; Eatough, Erin; Sundermann, Erin; Drogos, Lauren; Savarese, Antonia; Maki, Pauline M.
Abstract : Oral contraceptive (OC) users typically show a blunted or no cortisol response to psychosocial stress. Although most OC regimens include both an inactive (dummy) and active pill phase, studies have not systematically investigated cortisol responses during these pill phases. Further, high levels of cortisol following a stressor diminish retrieval of emotional material, but the effects of stress on memory among OC users are poorly understood. We examined the effects of a psychosocial stressor, the Trier Social Stress Test, vs. a control condition on cortisol responsivity and emotional memory retrieval in women tested either during their active ( n  = 18) or inactive pill phase ( n  = 21). In secondary analyses, we quantitatively compared OC users with normally cycling women and showed a significant lack of cortisol response during both active and inactive pill phase. Emotional recall did not differ between active and inactive pill phases. Stress differentially diminished recall of negative words compared with positive or neutral words, but cortisol levels were unrelated to memory performance. These findings indicate that OC users have distinct cortisol and memory responses to stress that are similar between the active and inactive pill phases. © 2016 Wiley Periodicals, Inc. Abstract : In response to a psychosocial stressor, oral contraceptive (OC) users showed no cortisol response and decreased recall of negative stimuli that was maintained during both the active and inactive pill phases. OC use generally may buffer against retrieval of negative memories following stress.